1976
DOI: 10.1111/j.1365-2818.1976.tb02402.x
|View full text |Cite
|
Sign up to set email alerts
|

The possibility of electron microscopic autoradiography of steroids after freeze drying of unfixed testes

Abstract: SUMMARY A technique has been developed for the autoradiographic localization of steroids in testes at the light and possibly electron microscope level. During processing of the tissue there is no contact of tissue with water up to the moment of photographic development of the autoradiographs. Tritium labelled steroids have been introduced into the testis through perfusion of the isolated organ. Small tissue samples were rapidly frozen, freeze dried and fixed with osmium vapour. The fixed tissue was embedded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A specially designed desiccator [7,8] was evacuated (about 1 Pa), after which the lid from the sample holder was lifted with a manipulator. Osmium tetroxide (OsO 4 ) vapor was admitted to the working chamber by opening a side port containing 0.1 g solid OsO 4 .…”
Section: Sample Preparationmentioning
confidence: 99%
“…A specially designed desiccator [7,8] was evacuated (about 1 Pa), after which the lid from the sample holder was lifted with a manipulator. Osmium tetroxide (OsO 4 ) vapor was admitted to the working chamber by opening a side port containing 0.1 g solid OsO 4 .…”
Section: Sample Preparationmentioning
confidence: 99%
“…15,this VoL), but the statistics for autoradiography generally require many more sections to obtain reliable data. On a cryoultramicrotome rather smooth thin sections were obtained by sectioning this material at -70°C (Frederik and Klepper 1976), sections which have been employed for the autoradiographic localization at the electron microscope level of steroids in testis (Frederik et al 1977). Thin cryosections from fresh-frozen (no chemical fixation) tissue are the most versatile specimens for studying the localization of diffusible substances by X-ray microanalysis or by autoradiography.…”
Section: Discussionmentioning
confidence: 99%
“…If the viscosity of the embedding resin is low enough, it is possible to directly infiltrate freeze-dried tissue without diluting the resin with an organic solvent. Several studies have demonstrated the utility of such an approach for the preservation of both ultrastructure and the chemical composition of tissues (Frederik and Klepper, 1976;Ingram, 1980, 1984;McGuffee et al, 1979McGuffee et al, ,1981McGuffee et al, ,1985. Since a primary chemical fixation is a n optional step before freezing (Chiovetti et al, 19861, it is possible to quick-freeze either fixed or unfixed tissue and to avoid all solvent dehydration by freeze-drying.…”
Section: Introductionmentioning
confidence: 99%